Effect of Electrical Double Layer on Stability Mechanism of the Cluster of Bulk Nanobubbles - Wang, Qiongyao (Langmuir : the ACS journal of surfaces and colloids, 2025)
Nanobubbles (NBs) hold significant promise in the fields of water treatment and environmental remediation due to their remarkable stability and longevity. Despite evidence of the stability of bulk nanobubbles (BNBs) in water, the underlying mechanisms of their stability remain elusive, with a notable gap in understanding the role of surface electronegativity in NBs' stability. In this work, an all-atom (AA) molecular dynamics (MD) simulation has been used to investigate the stability characteristics of individual BNBs and the aggregation behavior of double BNB clusters, incorporating the influence of the electrical double layer (EDL). The stability of individual BNBs is evaluated through analysis of the gas-liquid interface's high-density layer, the structure of the EDL, and the hydrogen bond (HB) network. A stabilization mechanism is proposed based on the surface electronegativity of BNBs. Meanwhile, the simultaneous construction of a double BNBs stability model reveals that nanobubble aggregation is the result of a competitive mechanism of van der Waals gravity and electrostatic repulsion. The validity of the proposed model is also verified by comparing the particle size and zeta tests of BNB solutions prepared with two gases with the nanobubble diameters and electrostatic energy obtained from the simulation model. A critical distance of 10 Å is determined, beyond which BNBs are less likely to coalesce. It is observed that the majority of BNBs are influenced by significantly greater electrostatic forces compared to the van der Waals force, which is hypothesized to be the main contributor to their stability